Pelatihan Pembuatan Media Pembelajaran ICT Di Rumah Ilmu Klakahrejo Surabaya - Salamah, Evi Rizqi; Rifayanti, Zuni Eka Tiyas (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Learning media is a tool to convey a message in the learning process. In order for this material to be understood and attract students, it must be realized. In fact, the teachers at Rumah Ilmu Klakahrejo are less able to design, make learning media so that they do not give concrete examples in delivering materials at the time of learning, the learning activities held by teachers are still dominated by storytelling, there are limited time and knowledge to create media, so that students only listen to the material delivered by the teacher, this results in students looking passive and lackluster. Therefore, the author proposes a solution by providing training to teachers at Rumah Ilmu Klakahrejo to create learning media, because this is one part of modeling techniques that can attract students' attention, increase motivation, and others. So that students can see, feel, and demonstrate in real life not in imagination or wishful thinking. This pegabdian aims to improve the skills and understanding of the making of learning media, with the aim to be able to improve the skills of teachers in media making. The external target in this study in the form of learning media from teachers and the results of this training is to make teachers in Rumah Ilmu Klakahrejo become skilled in creating and designing learning media